TEACHING SUBJECTS MATTER THROUGH ENGLISH AS THE MEDIUM OF INSTRUCTION IN THE NAMIBIAN ENGLISH SECOND LANGUAGE CLASSROOMS - Liswani Simasiku; Choshi Kasanda; Talita Smit (European Scientific Journal, ESJ, 2015)
Many Namibians haveindicated that both teachers and learners were not conversant enough to teach and learn schools subjects through the English medium. Furthermore, they have attributed learners’ poor performance in examinations to the use of English as the medium. Nonetheless, English has remained as the official medium of instruction in Namibian schools.This study sought to find out why the Namibian government had stuck to the use of English as medium of instruction in Namibian classrooms in view of the concerns raised by the teachers, learners and other stakeholders. The sample comprised 12 teachers at 12 schools in the Caprivi Educational Region.The results showed that English Second Language (ESL) teachers were of the view that the use of English as medium of instruction affected learners’ participation in English lesson and that it impacted negatively on learners’ end of year results.